Spaces, Places, and Geographies of Public Spheres: Exploring Dimensions of the Spatial Turn - Waldherr, Annie (2021)
For decades, scholars have been calling out a spatial turn in media and communication studies. Yet, in public sphere research, spatial concepts such as space and place have mainly been used metaphorically. In recent years, the abundance of digital trace data offers new opportunities to locate communicative interactions, sparking new interest in the spatial turn in media and communication and opening up new perspectives on spaces and places also within public sphere research. Digital location data enables one to: study the places and spaces in which (semi-)public communication is embedded; uncover geographical inequalities between countries, regions, cities, and peripheries; and highlight the local contexts of public spheres. This thematic issue gathers some of these endeavors in one place, bringing together conceptual, methodological, and empirical contributions that spell out the spatiality of public spheres in detail and combine the analysis of spaces, places, and geographies with long-standing concepts of public sphere research.